2002
DOI: 10.1002/1521-3773(20021018)41:20<3901::aid-anie3901>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Catalytic Synthesis of Substituted Allenes Using Indium

Abstract: Since allenes are versatile building blocks both for organic synthesis [1] and in transition-metal-promoted carbon±carbon bond-forming reactions, [2] development of practical methods for their preparation is of great interest. Allene moieties can be prepared by alkylation of allenylmethyl halides with an appropriate carbanionic species, [1e] by S N 2'-type selective displacement of propargyl alcohol derivatives with organocopper reagents, [1e, 3] and by intramolecular regio-and stereoselective reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(45 citation statements)
references
References 3 publications
(3 reference statements)
0
45
0
Order By: Relevance
“…Recrystallization using methylene chloride and n-hexane gave 3a (74.0 mg, 96%) as a white solid. 3, 171.3, 141.4, 135.5, 135.4, 129.6, 128.4, 128.1, 127.4, 116.2, 46.2, 40.0, 29.4, 17.0;IR (film) 2951IR (film) , 1731IR (film) , 1434IR (film) , 1241IR (film) , 1060 5,171.3,141.3,137.0,135.0,134.4,128.5,127.6,127.3,116.0,47.7,40.3,29.8,22.9,13.3;IR (film) 197.0, 196.9, 142.9, 137.1, 136.4, 135.1, 134.4, 134.3, 134.1, 133.8, 128.3, 127.7, 126.9, 126.8, 127.7, 113.7, 54.8, 47.8, 32.8, 22.1, 14.0; IR (film) 3060, 1695, 1594, 703 cm C NMR (100 MHz, CDCl 3 ) δ 170. 5, 138.1, 136.0, 135.6, 131.3, 128.4, 128.3, 127.5, 111.1, 68.0, 61.2, 21.2, 14.3, 13.8;IR (film) 2975IR (film) , 1739IR (film) , 1609IR (film) , 1465IR (film) , 1130 8, 143.4, 141.0, 136.6, 134.6, 128.2, 127.7, 126.6, 110.1, 60.4, 40.2, 35.8, 35.1, 21.9, 14.3, 14.2;IR (film) 2932IR (film) , 1732IR (film) , 1442IR (film) , 1178IR (film) , 1038 9, 143.8, 140.5, 137.9, 133.7, 128.1, 127.6, 126.4, 111.1, 60.4, 47.5, 31.1, 25.7, 22.2, 14.3, 13.9;IR (film) 2931IR (film) , 1732IR (film) , 1605IR (film) , 1443IR (film) , 1373IR (film) , 1308IR (film) , 1258IR (film) , 1155IR (film) , 1040 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recrystallization using methylene chloride and n-hexane gave 3a (74.0 mg, 96%) as a white solid. 3, 171.3, 141.4, 135.5, 135.4, 129.6, 128.4, 128.1, 127.4, 116.2, 46.2, 40.0, 29.4, 17.0;IR (film) 2951IR (film) , 1731IR (film) , 1434IR (film) , 1241IR (film) , 1060 5,171.3,141.3,137.0,135.0,134.4,128.5,127.6,127.3,116.0,47.7,40.3,29.8,22.9,13.3;IR (film) 197.0, 196.9, 142.9, 137.1, 136.4, 135.1, 134.4, 134.3, 134.1, 133.8, 128.3, 127.7, 126.9, 126.8, 127.7, 113.7, 54.8, 47.8, 32.8, 22.1, 14.0; IR (film) 3060, 1695, 1594, 703 cm C NMR (100 MHz, CDCl 3 ) δ 170. 5, 138.1, 136.0, 135.6, 131.3, 128.4, 128.3, 127.5, 111.1, 68.0, 61.2, 21.2, 14.3, 13.8;IR (film) 2975IR (film) , 1739IR (film) , 1609IR (film) , 1465IR (film) , 1130 8, 143.4, 141.0, 136.6, 134.6, 128.2, 127.7, 126.6, 110.1, 60.4, 40.2, 35.8, 35.1, 21.9, 14.3, 14.2;IR (film) 2932IR (film) , 1732IR (film) , 1442IR (film) , 1178IR (film) , 1038 9, 143.8, 140.5, 137.9, 133.7, 128.1, 127.6, 126.4, 111.1, 60.4, 47.5, 31.1, 25.7, 22.2, 14.3, 13.9;IR (film) 2931IR (film) , 1732IR (film) , 1605IR (film) , 1443IR (film) , 1373IR (film) , 1308IR (film) , 1258IR (film) , 1155IR (film) , 1040 …”
Section: Methodsmentioning
confidence: 99%
“…4 Recently, we have demonstrated that allenylindiums generated in situ from indium and propargyl bromides are effective cross-coupling partners in palladiumcatalyzed cross-coupling reactions to produce substituted allenes in excellent yields. 5 In continuation of our studies directed toward preparative method of vinyl allenes with allenyindium, we describe herein the Diels-Alder reaction of vinyl allenes possessing 3,4-and 4,5-disubstituents and ketone group with a variety of dienophiles to give cyclic compounds having exo-methylene group (Scheme 1).First, 3-methyl-4-phenyl-1,2,4-pentatriene (1a) as vinyl allene was prepared from the reaction of α-bromostyrene with allenylindium obtained from indium and 1-bromo-2-butyne and then, the Diels-Alder reactions with dienophiles were examined to obtain cyclic compounds having exomethylene group. The results are summarized in Table 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The diester 279 is also obtained when unsubstituted malonate 280 is treated with excess 2-chloro-1,3-butadiene ( 281 , chloroprene) and 2.5 equiv of sodium methoxide in the presence of Pd/DPEphos [167]. Another Pd-mediated coupling experiment, leading to a derivative of 266 involves the dibromide 282 and the aromatic haloester 283 ; the bisallene derivative 284 was obtained in 68% yield [168]. …”
Section: Reviewmentioning
confidence: 99%
“…4) in DMF-d7 at room temperature (ratio of these two reagents; 1:6.5). 10 On the basis of this result, Chan found that the reaction of indium with propargyl bromide produced allenylindium in water. 11 But, this reaction in THF gave the mixture of allenylindium and allenylindium dibromide (eq.…”
mentioning
confidence: 99%